Profile of the agricultural cooperatives of Unicafes system - Mazutti Zanco, Alcidir; Guimarães Zanco, Rosane Aparecida; Alves, Adilson Francelino (Universidade Federal Rural do Rio de Janeiro, 2020)
Agricultural cooperatives represent a strong social and economic segment. This organizational branch carries out actions in the social, productive, agroindustrial and commercial fields, accounting for approximately 10% of the Brazilian GDP (Gross Domestic Product) and 40% of the agricultural sector exports, significant numbers, which bring together initiatives from two productive sectors. The first and strongest is represented by rural employers, a productive segment that develops traditional monocultures, associated with medium and large cooperatives. The second, recently organized, is represented by family farming, a productive segment that develops a diversified agriculture model, associated with smaller cooperatives, entitled “solidarity”. This research systematizes data of cooperatives that are present in different regions of Brazil and was carried out in 2018, with revision in 2019, aiming to analyze the organizational differentials present in the profile of Agricultural Cooperatives of the solidarity model, using the Clusters method as exploratory and descriptive tool to group networks into similar conglomerates according to membership, organizational structure, revenue and access to public policy. The analysis of this organizational model results in the formation of two conglomerates with considerable degrees of dissimilarity, validating the claim that the foundational base and the associated public do not define the model and the viability of the cooperative organization.